2014
DOI: 10.1584/jpestics.j14-05
|View full text |Cite
|
Sign up to set email alerts
|

Research and development of a novel insecticide, flonicamid

Abstract: Flonicamid, a novel class insecticide possessing a unique chemical structure, was discovered in 1992, developed by Ishihara Sangyo Kaisha, Ltd., and registered in Japan in 2006 under the trade name of Ulala DF. This compound is very active against a wide range of aphid species and also is effective against some other species of sucking insects. It rapidly inhibits the feeding behavior of aphids and provides long-lasting control. Flonicamid shows no cross-resistance to conventional insecticides and exhibits exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…Flonicamid acts in the aphid nervous system, disrupting the function of chrodotonal stretch receptor organs, the target site not defined as yet. Although the insecticidal properties of flonicamid (antifeedant activity) resemble those of pymetrozine, the two insecticides have different MoA (Group 29 vs. Group 9) (Morita et al ., 2007, 2014). In addition, flonicamid is a selective insecticide with null to low toxicity to beneficial arthropods (Jansen et al ., 2011; Morita et al ., 2014), and due to its antifeedant activity it can be used against aphid-transmitted plant viruses.…”
Section: Other Aphicidesmentioning
confidence: 99%
“…Flonicamid acts in the aphid nervous system, disrupting the function of chrodotonal stretch receptor organs, the target site not defined as yet. Although the insecticidal properties of flonicamid (antifeedant activity) resemble those of pymetrozine, the two insecticides have different MoA (Group 29 vs. Group 9) (Morita et al ., 2007, 2014). In addition, flonicamid is a selective insecticide with null to low toxicity to beneficial arthropods (Jansen et al ., 2011; Morita et al ., 2014), and due to its antifeedant activity it can be used against aphid-transmitted plant viruses.…”
Section: Other Aphicidesmentioning
confidence: 99%
“…Additionally, flonicamid is a systemic insecticide and can be readily transported from roots to the leaves of cotton. 26,27 Third, AMF could alter rhizosphere properties, [38][39][40] then directly or indirectly affect the availability of flonicamid, and increase uptake efficiency. Some studies showed that AMF secrete organic substances to change the properties of the surrounding soil and affect the availability of nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…Flonicamid is a new novel systemic insecticide with high activity against Aphis gossypii Glover and low toxicity to non-target organisms. [25][26][27] Flonicamid can inhibit the feeding behavior of aphids in less than 30 min of treatment, and the antifeeding activity is not recoverable until death 26 Our previous studies showed that flonicamid applied via drip irrigation can be absorbed by cotton roots and easily transported to leaves, resulting in effective control of cotton aphid over a prolonged period. 14 To overcome the loss of active ingredient by soil adsorption, the dosage of drip-applied flonicamid needs to be higher compared with that for a foliar spray.…”
Section: Introductionmentioning
confidence: 99%
“…The higher efficacy of spinosad and chlorfenapyr may be associated with their modes of action. For example, flonicamid is a selective feeding blocker (IRAC designation 29) causing starvation by inhibiting the ingestion of phloem (Cho et al, 2011;Morita et al, 2014). However, this mode of action may increase the time required to kill western flower thrips adults, especially in cut flowers.…”
Section: Discussionmentioning
confidence: 99%